Metagenomic analysis reveals a dynamic microbiome with diversified adaptive functions to utilize high lignocellulosic forages in the cattle rumen - Gharechahi, Javad; Vahidi, Mohammad Farhad; Bahram, Mohammad; Han Jianlin; Ding, Xue-Zhi; Salekdeh, Ghasem Hosseini (Springer, 2021)
Rumen microbiota play a key role in the digestion and utilization of plant materials by the ruminant species, which have important implications for greenhouse gas emission. Yet, little is known about the key taxa and potential gene functions involved in the digestion process. Here, we performed a genome-centric analysis of rumen microbiota attached to six different lignocellulosic biomasses in rumen-fistulated cattle. Our metagenome sequencing provided novel genomic insights into functional potential of 523 uncultured bacteria and 15 mostly uncultured archaea in the rumen. The assembled genomes belonged mainly to Bacteroidota, Firmicutes, Verrucomicrobiota, and Fibrobacterota and were enriched for genes related to the degradation of lignocellulosic polymers and the fermentation of degraded products into short chain volatile fatty acids. We also found a shift from copiotrophic to oligotrophic taxa during the course of rumen fermentation, potentially important for the digestion of recalcitrant lignocellulosic substrates in the physiochemically complex and varying environment of the rumen. Differential colonization of forages (the incubated lignocellulosic materials) by rumen microbiota suggests that taxonomic and metabolic diversification is an evolutionary adaptation to diverse lignocellulosic substrates constituting a major component of the cattle’s diet. Our data also provide novel insights into the key role of unique microbial diversity and associated gene functions in the degradation of recalcitrant lignocellulosic materials in the rumen.